Long-term complications and prognosis of chronic beryllium disease - Handa, T.; Nagai, S.; Kitaichi, et al., M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background: Chronic beryllium disease (CBD) is a rare disease, and there are no previous reports that have followed CBD patients over several decades. Thus, the long-term complications and prognosis of this illness still remain unclear. Objective: The aim of this study was to investigate long-term complications and prognosis of CBD patients. Study design and Methods: This was a retrospective study based on the medical records of all CBD patients diagnosed at Kyoto University Hospital between the period 1973 to the present day. Ultimately, ten patients whose diagnoses had been made during the period 1973 to 1977 were included. Long-term physiological and radiological change, complications and prognosis of these patients were investigated. Results: Three patients completely remitted, and one died of cor-pulmonale. Among the remaining six patients, four have been followed up for more than thirty years in our institute. The majority developed mixed patterns of lung function impairment, cavity lesions of the lung, pneumothorax, and respiratory infections. Conclusions: Long-term prognosis of CBD was poor with several complications due to chronic parenchymal and airway lesions.